2019
DOI: 10.20473/jphrecode.v3i1.14628
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Lingkungan Kerja dengan Gejala Sick Building Syndrome pada Pegawai BPJS Kesehatan Depok Tahun 2019

Abstract: Sick building syndrome (SBS) merupakan kumpulan keluhan yang dirasakan oleh pegawai yang bekerja di dalam ruangan dengan kualitas udara yang kurang baik. Pegawai BPJS Kesehatan Kota Depok bekerja dalam ruangan yang tertutup dengan pencahayaan dan iklim kerja yang kurang baik sehingga berpotensi mengalami gejala seperti kelelahan, sakit kepala, dan nyeri punggung. Tujuan penelitian ini menganalisis hubungan lingkungan kerja dengan gejala Sick Building Syndrome pada pegawai BPJS Kesehatan Kota Depok tahun 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
1
4
0
2
Order By: Relevance
“…Moreover, the results of statistical tests about the period of work and the incidence of SBS show that there was no relationship between tenure and the incidence of SBS, having a p value ≥ 0.05. The results of this study is consistent with research by Annisa sstating that there was no significant relationship between work period and the incidence of SBS (p = 1.000) (Asri, 2019).…”
Section: Sick Building Syndrome Incidencesupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the results of statistical tests about the period of work and the incidence of SBS show that there was no relationship between tenure and the incidence of SBS, having a p value ≥ 0.05. The results of this study is consistent with research by Annisa sstating that there was no significant relationship between work period and the incidence of SBS (p = 1.000) (Asri, 2019).…”
Section: Sick Building Syndrome Incidencesupporting
confidence: 92%
“…Moreover, there is a relationship between demographic factors, which are age factors (p-value 0.014), work related factors, and ventilation system (air flow velocity) (p-value 0.036), with sick building syndrome symptoms in workers (Saffanah and Pulungan, 2017). A study conducted by Asri (2019) showed that there was a relationship between lighting (p = 0.001), age (p = 0.006), psychosocial conditions (0,025), smoking habits (p = 0,025), and history of disease (p=0,038) with symptoms of SBS.…”
Section: Introductionmentioning
confidence: 99%
“…) that the incidence symptoms of SBS experienced is below 50% of the symptoms felt. However, there is a difference between the results of research by Asri et al (2019) that the incidence of SBS is more than 50%. According to Suma'mur (2013) that SBS events occur due to poor design, operation, and maintenance of buildings so they pay less attention to comfort in buildings such as temperature, humidity, airflow, and lighting which can cause symptoms of SBS (Table 2).…”
Section: Symptoms Of Sick Building Syndromementioning
confidence: 89%
“…The Occupational Safety and Health Administration (OSHA) explains that indoor air quality is disturbed due to inadequate ventilation (52%), sources of contamination indoors (16%) and outdoors (10%), presence of microbes (5%), contaminated materials from building materials (4%), and others (13%) (Michaels et al, 2020). This situation can be exacerbated if the building uses an Air Conditioner (AC) that is not maintained (Asri et al, 2019). According to the Environmental Protection Agency of America (EPA), buildings that use air conditioning can grow Legionella pathogenic bacteria which can cause Legionellosis disease and SBS (Adiningsih et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…17 Sementara, penelitian Asri menyatakan sebaliknya, dimana hasil penelitiannya menunjukkan bahwa faktor umur berhubungan dengan gejala SBS yang dialami oleh pegawai yang berumur <30 tahun karena sering menghabiskan waktu di dalam gedung akibat banyaknya pekerjaan yang harus dilakukan. 18 Sama seperti halnya hasil penelitian ini yang juga menunjukkan bahwa karyawan yang lebih muda (≤40 tahun) lebih banyak menghabiskan waktu di tempat kerja dalam waktu yang cukup lama (lebih dari 8 jam/hari) untuk menyelesaikan pekerjaannya.…”
Section: Pendahuluanunclassified